SEPATU COMPASS : PRODUK LOKAL RASA DUNIA - Ma’rifatul Ulya; Mirza Mirza Dwinanda Ilmawan; Aditya Narendra Wardhana; Lanal Abrori Himawan (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2022)
The purpose of this study was to determine consumer behavior based on factors that influence consumers to make decisions in purchasing Compass Shoes. Data collection techniques through observation, interviews, and documentation. This study used a sample of informants in Gresik who met the criteria, namely having Compass shoes and getting them through their own efforts. The theoretical basis used in this research is the Consumer Decision Making Behavior Model and the Influencing Factors ranging from environmental factors, individual differences, psychological processes to decision making processes. The results of this study indicate that consumers of Compass shoes are willing to queue to fulfill their desires and have products that are experiencing an increase in value.